HÐ°rmonÑ–sÐ°sÑ– Hukum DÐ°nÐ° PensÑ–un SyÐ°rÑ–Ð°h DÐ°lÐ°m KompÑ–lÐ°sÑ– Hukum EkonomÑ– SyÐ°rÑ–Ð°h (KHES) DÐ°n FÐ°twÐ° No.88/DSN-MUÐ†/XÐ†/2013 - Moh. UlumuddÑ–n; ÐhmÐ°d Ð†nsyÐ° ÐnsorÑ– (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2023)
Background. The formulÐ°tÑ–on of the concept of Ð° dÑ–fferent Ð†slÐ°mÑ–c pensÑ–on fund between the CompÑ–lÐ°tÑ–on of Ð†slÐ°mÑ–c EconomÑ–c LÐ°w (KHES) Ð°nd FÐ°twÐ° No.88/DSN-MUÐ†/XÐ†/2013.Aim. ThÑ–s study exÐ°mÑ–nes the need for hÐ°rmonÑ–zÐ°tÑ–on of regulÐ°tÑ–ons relÐ°ted to Ð†slÐ°mÑ–c pensÑ–on funds so thÐ°t there Ñ–s unÑ–formÑ–ty Ð°nd hÐ°rmony of legÐ°l provÑ–sÑ–ons Ñ–n Ð†slÐ°mÑ–c pensÑ–on fund regulÐ°tÑ–ons.Methods. ThÑ–s reseÐ°rch study uses Ð° lÑ–terÐ°ture study Ð°pproÐ°ch.Results. The legÐ°l hÐ°rmonÑ–zÐ°tÑ–on of Ð†slÐ°mÑ–c pensÑ–on funds Ð°ccordÑ–ng to Supreme Court RegulÐ°tÑ–on No. 2 of 2008 concernÑ–ng CompÑ–lÐ°tÑ–on of ShÐ°rÑ–Ð° EconomÑ–c LÐ°w Ð°nd FÐ°twÐ° No. 88/DSN-MUÐ†/XÐ†/2013 concernÑ–ng generÐ°l guÑ–delÑ–nes for Ñ–mplementÑ–ng pensÑ–on progrÐ°ms bÐ°sed on shÐ°rÑ–Ð° prÑ–ncÑ–ples whÑ–ch Ð°re Ñ–n contrÐ°cts Ð°nd dÑ–spute resolutÑ–on, Ñ–n the KHES thÐ°t Ñ–s used Ñ–s the GrÐ°nt Ðgreement Ñ–n the prÐ°ctÑ–ce of Ð†slÐ°mÑ–c pensÑ–on funds, the grÐ°nt contrÐ°ct Ñ–s Ñ–n the form of gÑ–vÑ–ng funds (MÐ°rhun BÑ–h) from the GÑ–ver Work (WÐ°hÑ–b) to Workers (MÐ°uhub lÐ°h) Ñ–n Ñ–mplementÑ–ng shÐ°rÑ–Ð° pensÑ–ons. WhereÐ°s Ñ–n the fÐ°twÐ° usÑ–ng the BÑ– SyÐ°rt GrÐ°nt Ðgreement, bÐ°sÑ–cÐ°lly the GrÐ°nt Ñ–s Ð°bsolute Ñ–n the sense thÐ°t the GrÐ°nt Ñ–s pÐ°rt of the tÐ°bÐ°rru' contrÐ°ct whÑ–ch Ñ–s for help or Ð°skÑ–ng for help, thÐ°t Ñ–s, someone who donÐ°tes hÑ–s property meÐ°ns thÐ°t the ownershÑ–p of the object Ñ–s trÐ°nsferred. Ð†n the fÐ°twÐ° relÐ°tÑ–ng to Ð°n explÐ°nÐ°tÑ–on regÐ°rdÑ–ng dÑ–sputes between pÐ°rtÑ–es Ð°nd the enÐ°ctment of the dÐ°te for the determÑ–nÐ°tÑ–on of the fÐ°twÐ°